Indications for neuromuscular ultrasound: Expert opinion and review of the literature. Issue 12 (December 2018) - Walker, Francis O.; Cartwright, Michael S.; Alter, Katharine E.; Visser, Leo H.; Hobson-Webb, Lisa D.; Padua, Luca; Strakowski, Jeffery A.; Preston, David C.; Boon, Andrea J.; Axer, Hubertus; van Alfen, Nens; Tawfik, Eman A.; et al.
Highlights: Experts routinely use ultrasound to evaluate both common and rare disorders of nerve and muscle. Accumulated evidence now puts diagnostic neuromuscular ultrasound on par with EMG and NCS. Medical centers must acquire ultrasound equipment to keep electrodiagnostic laboratories current. Abstract: Over the last two decades, dozens of applications have emerged for ultrasonography in neuromuscular disorders. We wanted to measure its impact on practice in laboratories where the technique is in frequent use. After identifying experts in neuromuscular ultrasound and electrodiagnosis, we assessed their use of ultrasonography for different indications and their expectations for its future evolution. We then identified the earliest papers to provide convincing evidence of the utility of ultrasound for particular indications and analyzed the relationship of their date of publication with expert usage. We found that experts use ultrasonography often for inflammatory, hereditary, traumatic, compressive and neoplastic neuropathies, and somewhat less often for neuronopathies and myopathies. Usage significantly correlated with the timing of key publications in the field. We review these findings and the extensive evidence supporting the value of neuromuscular ultrasound. Advancement of the field of clinical neurophysiology depends on widespread translation of these findings.